2008
DOI: 10.1007/s11284-008-0524-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the pericarp on imbibition, seed germination, and seedling establishment in seeds of Hedysarum scoparium Fisch. et Mey

Abstract: Four independent experiments were designed to investigate the effects of the pericarp on seed imbibition, dehydration, germination, seedling establishment, and seed longevity in the field in seeds of Hedysarum scoparium Fisch. et Mey. The results showed that the presence of the pericarp decreased seed imbibition rates in the first 6 h, but the seeds attained significantly higher final water content after 24 h of soaking. The pericarp caused seed dormancy, and removal of the pericarp improved the germination pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 11 publications
0
34
1
1
Order By: Relevance
“…Based on our results, the lemmas significantly increased the amount of water uptake, especially during the initial 10 h. This characteristic might protect the seeds under dry conditions because the seeds can absorb more water and increase the water use efficiency to resist the drought stress. However, this result is not in agreement with that of Hu, Wang & Wu (2009) for Hedysarum scoparium . This discrepancy might be the result of the different plant species, seed size, adaptive mechanism and living environments of the two species.…”
Section: Resultscontrasting
confidence: 89%
See 1 more Smart Citation
“…Based on our results, the lemmas significantly increased the amount of water uptake, especially during the initial 10 h. This characteristic might protect the seeds under dry conditions because the seeds can absorb more water and increase the water use efficiency to resist the drought stress. However, this result is not in agreement with that of Hu, Wang & Wu (2009) for Hedysarum scoparium . This discrepancy might be the result of the different plant species, seed size, adaptive mechanism and living environments of the two species.…”
Section: Resultscontrasting
confidence: 89%
“…Therefore, several research efforts have tried to explore how to remove the lemmas by artificial means and enhance the seed germination percentage of Leymus chinensis . However, certain researchers reported that the seed coat was assumed to be beneficial for long-term seed survival in the soil, especially in harsh, dry environments (Chacón & Bustamante, 2001; Hu, Wang & Wu, 2009). In the Songnen grassland of China, Leymus chinensis exists as the dominant species.…”
Section: Introductionmentioning
confidence: 99%
“…This delay in germination can favour the formation of a seed bank in the soil if seed viability is maintained. The structures surrounding the seeds, such as the endocarp and pericarp, were associated with delayed germination of primary tropical species (Hopkins & Graham 1987), and in some species, these structures play an important role in preventing water loss in seeds, thereby helping maintain the viability and extending the longevity of buried seeds (Lobova et al 2003;Hu et al 2009), including Lauraceae species (Chacón & Bustamante 2001). These roles may be particularly important for the formation of a seed bank in the soil in desiccation-sensitive species.…”
Section: Introductionmentioning
confidence: 99%
“…Although a flesh cover is beneficial for seed longevity in arid environments (Hu et al, 2009), it may delay rapid germination possibilities of recalcitrant seeds. The fresh 'intact fruit' (26%) germination success was as low as that of the stored 'true seed', indicating that humans, monkeys and other animals may be important in assisting the seed germination process when consuming the pulp.…”
Section: Tablementioning
confidence: 99%